Intervención del terapista respiratorio en paciente masculino de 6 años de edad con asma bronquial. - Yánez Lamilla, Lehybis Vicente (2022)
Bronchial asthma is a lung disease that causes inflammation and narrowing of the airways, which in turn makes it difficult to breathe. The main signs and symptoms of this disease are wheezing, cough, and chest tightness. The main triggers of bronchial asthma in the patient were due to environmental allergens to which he is exposed such as dust, mites, mold, among others, in addition to being a passive smoker because the patient's father is an active smoker and smokes indoors. the house and the patient inhales that smoke which is harmful to health and the cause of countless respiratory diseases, including bronchial asthma. The present investigation was established in the intervention of the respiratory therapist in a 6-year-old male patient diagnosed with bronchial asthma. which presented the following signs and symptoms dyspnea, cough, headache, chest tightness, and wheezing. The pharmacological treatment in the 6-year-old male patient diagnosed with bronchial asthma was based on the administration of bronchodilators and anti-inflammatory corticosteroids, the respiratory therapy techniques used in the patient were oxygen therapy through a simple mask and nebulizations.